PERAN TOKOH AGAMA DALAM MENINGKATKAN KESADARAN TERHADAP PANDEMI COVID-19 DI DESA SUMBER AGUNG KECAMATAN BUAY MADANG KABUPATEN OKU TIMUR - halimatus sa'diyah (Jurnal At-Taujih, 2021)
A religious figure is a person who does not get a formal appointment as a leader, but because he has a number of superior qualities, he reaches a position as a person who is able to influence the psychological condition and behavior of a group or society. While the role is the action taken by someone in an event. So it can be concluded that the role of religious leaders in raising awareness of the Covid-19 pandemic is also needed. The problems studied in this thesis are: 1) What are the roles of religious leaders in making people aware of the COVID-19 pandemic. 2) What are the obstacles faced by religious leaders in increasing awareness of the covid-19 pandemic in Sumber Agung Village. The aim is to find out the role of religious leaders in making people aware of the covid-19 pandemic and to find out the obstacles faced by religious leaders in increasing awareness of the covid-19 pandemic in Sumber Agung Village. In answering these problems, the researcher used a qualitative type of research using a descriptive qualitative approach. With this research, the writer tries to reveal the circumstances or phenomena that are in accordance with the reality that exists in Sumber Agung Village. Data collection techniques using the method of observation, interviews, and documentation. The subjects that I studied in this study used a purposive sampling technique, namely, 3 religious leaders, and 3 people from Sumber Agung Village. Meanwhile, data analysis includes data reduction, data presentation, and drawing conclusions. The results of this study are that religious leaders in raising awareness of the Covid-19 pandemic in Sumber Agung Village have three strategic roles, namely the role of education, the role of enlightenment, and the role of building the system. The obstacle of religious leaders in increasing public awareness about the corona virus problem in Sumber Agung Village is still not optimal, due to the lack of support from the government and there are still many people who do not understand the Covid-19 pandemic itself.